2016
DOI: 10.31018/jans.v8i1.810
|View full text |Cite
|
Sign up to set email alerts
|

Productivity enhancement and popularization of improved production technologies in wheat through frontline demonstrations

Abstract: Front line demonstrations (FLDs) on wheat were conducted on 150 farmers’ fields to demonstrate the impact of drought tolerant rainfed varieties (PBW 175 & PBW 644) and other improved practices techniques (supplemental irrigation and sowing with seed drill) on production and economic benefits in the kandi region of Punjab state during rabi seasons from 2011-12 to 2013-14 under rainfed situation. The improved production technologies recorded additional mean yield of 27.8 q/ha and 28.4 q/ha for rainfed vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
12
1
0
Order By: Relevance
“…More and more use of latest production technologies with high yielding varieties will subsequently change this alarming trend of galloping extension gap. These results are in close conformity with that of reported by Verma et al, (2014) and Sharma et al, (2016).…”
Section: Extension Gapsupporting
confidence: 94%
See 2 more Smart Citations
“…More and more use of latest production technologies with high yielding varieties will subsequently change this alarming trend of galloping extension gap. These results are in close conformity with that of reported by Verma et al, (2014) and Sharma et al, (2016).…”
Section: Extension Gapsupporting
confidence: 94%
“…However, the variations in the yield were observed over the years and it attributed the climatic conditions and incidence of disease and pests. These results are in close conformity with the research findings reported by Sharma et al, (2016).…”
Section: Wheat Yieldsupporting
confidence: 93%
See 1 more Smart Citation
“…Ashok Kumar, Maya Kumari, Nidhi Sinha, Govind Kumar, Anil Kumar It was also found that the demonstrated technologies under FLD resulted in an increase in yield by 19.15% over Local Check. The results found to be in close conformity with the research results of (Sharma et al, 2016, Singh S. B., 2017. Table 1 Showed mean extension gap of 4.96q/ ha which is the gap between demonstrated technology and local check.…”
Section: International Journal Of Agricultural Invention 3(1): 2018supporting
confidence: 84%
“…Findings of the study in accordance with Arvind kumar, (2017), Balai et al, (2012Iqbal et al, (2017), Rao et al, (2011) and Sharma et al, (2016). For economic parameters, cost of cultivation for IT and FP were calculated (…”
Section: Technological Index (Ti)supporting
confidence: 74%